Comparative study between furnace brazing and laser brazing - Y. Erny, A. M. Y.; Fadhil, A. R.; Aiman, Mohd Halil; Mahadzir, Ishak; Quazi, M. M. (IOP Publishing, 2021)
Nowadays, brazing has been widely used in many industries, especially in the automotive application. The brazing process is introduced as it can be used to join the different metals together without melting the parent material. In this present study, furnace brazing and laser brazing of Ti-6Al- 4V titanium alloy and 316 L stainless steel (SS) with silver-based, BAg 8-1.5Ti filler metal were studied. There are significantly different between furnace brazing, also known as conventional brazing method and laser brazing in terms of joining strength and microstructure reaction. Furnace brazing was performed at 870°C and 880°C with 30 minutes of heating duration. Meanwhile, laser brazing was performed using a 200Watt continuous wave laser with varying laser power. Both of brazing method was conducted with a vacuum pressure of 3×10−3 Pa. Besides, to maintain the accuracy of the temperature measurement of laser brazing, an infrared thermometer is used. The tensile test was conducted to analyse the mechanical properties. The cross-sections of the brazed joints have been examined using an optical microscope. The brazed joints of the furnace brazing show an average tensile strength of 55.89 kPa for 880°C and 43.16 kPa for 870°C. Nonetheless, the maximum tensile strength of laser brazed joints was 27.95 kPa, which is lower than furnace brazed joints.